2009
DOI: 10.1073/pnas.0903234106
|View full text |Cite
|
Sign up to set email alerts
|

Pentamidine reverses the splicing defects associated with myotonic dystrophy

Abstract: Myotonic dystrophy (DM) is a genetic disorder caused by the expression (as RNA) of expanded CTG or CCTG repeats. The alternative splicing factor MBNL1 is sequestered to the expanded RNA repeats, resulting in missplicing of a subset of pre-mRNAs linked to symptoms found in DM patients. Current data suggest that if MBNL1 is released from sequestration, disease symptoms may be alleviated. We identified the small molecules pentamidine and neomycin B as compounds that disrupt MBNL1 binding to CUG repeats in vitro. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
306
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 234 publications
(317 citation statements)
references
References 49 publications
(63 reference statements)
4
306
2
Order By: Relevance
“…A potential alternative approach is to use combined administration of CAG morpholinos with gapmers targeting different sequences within the DMPK mRNA to avoid binding competition. In addition, several reports have identified small molecules and peptides with the ability to disrupt RNA foci formation (31,32). This opens up the possibility of combining ASOs with other nonantisense strategies for DM1 therapy.…”
Section: Discussionmentioning
confidence: 99%
“…A potential alternative approach is to use combined administration of CAG morpholinos with gapmers targeting different sequences within the DMPK mRNA to avoid binding competition. In addition, several reports have identified small molecules and peptides with the ability to disrupt RNA foci formation (31,32). This opens up the possibility of combining ASOs with other nonantisense strategies for DM1 therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Significantly, CUG focus formation requires the binding of the alternative splice factor, muscleblind 1 (MBNL1) to the expanded CUG repeat expansions (11,12). The importance of the aberrant MBNL1-CUG interaction in DM1 is underscored by the use of pentamidine and morpholino antisense oligonucleotides that dislodge MBNL1 from expanded CUG RNA, restore free MBNL1 levels, and rescue splice defects in DM1 mouse models (13,14). Consistent with these observations, inactivation of Mbnl1 in mice recapitulates a large fraction of the splice defects and several key features of DM1 pathology (15,16).…”
Section: Myotonic Dystrophy I (Dm1)mentioning
confidence: 99%
“…This demonstrates that the suppression of CUG-dependent phenotypes and recovery of Mbnl1 activity can be achieved without directly competing with Muscleblind binding to CUG repeats but by reducing the fraction of double-stranded CUG RNA from the cellular pool of toxic RNA, hence preventing sequestration of the protein, which requires CUG RNA hairpins. This is a unique mechanism that contrasts with that of other recently characterized molecules that target the binding of MBNL1 to toxic RNAs (17)(18)(19)(20)(21)(22)33). Disrupting Muscleblind binding to RNA could affect its function as a splicing factor in non-CUG-expressing cells.…”
Section: Abp1 Reversed Missplicing and Muscle Histopathology In A Dm1mentioning
confidence: 62%
“…They demonstrated that expanded CTG-induced effects could be reverted if CTG-repeat transgene expression was interrupted in a DM1 mouse model. Several other groups developed synthetic molecules and (CAG)n oligonucleotides that disrupted MBNL1 interaction with expanded CUG repeats (17)(18)(19)(20)(21)(22). However, those approaches may not address all the pathological consequences of expanded CUG RNAs.…”
mentioning
confidence: 99%